Organic shrinkage inhibitor for lead-acid batteries and its manufacturing method

The use of ultrafiltrated lignin sulfonic acid as an antishrinkage agent in lead-acid batteries addresses the challenge of maintaining discharge characteristics while improving charge acceptance, resulting in enhanced battery performance.

JP7603056B2Active Publication Date: 2024-12-19NIPPON PAPER IND CO LTD
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
JP2022507159
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-09
Filing Date
2021-03-08
Publication Date
2024-12-19
Estimated Expiration
2041-03-08

AI Technical Summary

Technical Problem

Lead-acid batteries face challenges in maintaining discharge characteristics while improving charge acceptance due to the nature of lignin added to the negative electrode, which enhances high-rate discharge but decreases charge acceptance.

Method used

An organic antishrinkage agent for lead-acid batteries is produced by ultrafiltrating sulfite cooking black liquor using an ultrafiltration membrane to reduce substances with a molecular weight of 5,000 or less to 30% by mass, utilizing lignin sulfonic acid with controlled methoxyl group content and reducing sugars, and adding it to the negative electrode.

Benefits of technology

The solution improves charge acceptance while maintaining discharge characteristics, enhancing the performance of lead-acid batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603056000001
    Figure 0007603056000001
  • Figure 0007603056000002
    Figure 0007603056000002
Patent Text Reader

Abstract

This organic shrink-proofing agent for lead acid storage batteries contains a lignin sulfonic acid, and is characterized in that: the content of reducing sugars per the solid content is 5% by mass or less of the whole; and the content of substances having a molecular weight of 5,000 or less per the solid content is 30% by mass or less of the whole. This method for producing the organic shrink-proofing agent for lead acid storage batteries is characterized by having a step wherein a sulfite cooking black liquor is subjected to an ultrafiltration treatment with use of an ultrafiltration membrane and the thus-obtained concentrated sulfite cooking black liquor is recovered.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an organic shrinkage preventer for lead-acid batteries. [Background technology]

[0002] Lead-acid batteries are relatively inexpensive and have stable performance as secondary batteries, and therefore have been widely used as automobile batteries, batteries for portable devices, computer backup batteries, communications batteries, and the like.

[0003] When a lead-acid battery changes from a discharged state to a charged state as a result of repeated charging and discharging, the negative electrode active material shrinks, reducing the specific surface area and causing a deterioration in discharge performance. In addition, in the negative electrode active material, metallic lead releases electrons and changes to lead sulfate in the discharge reaction, and lead sulfate gains electrons and changes to metallic lead in the charge reaction. However, if the lead sulfate becomes coarse, it becomes difficult for the lead sulfate to dissolve in the charge reaction, causing a deterioration in charge performance.

[0004] It has been proposed to add lignin extracted from wood as an organic shrinkage preventer to the negative electrode active material of a lead-acid battery in order to prevent the shrinkage of the negative electrode active material (Patent Documents 1 to 3).

[0005] In addition, several types of lignin have been disclosed as lignin for lead-acid batteries (Patent Documents 4 to 11). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] USPat.No.2371136 [Patent Document 2] USPat.No.3523041 [Patent Document 3] Japanese Unexamined Patent Publication No. 62-145655 [Patent Document 4] JP 2002-117856 A [Patent Document 5] WO2002 / 039519 publication [Patent Document 6] JP 2005-294027 A [Patent Document 7] JP 2007-165273 A [Patent Document 8] Japanese Patent Application Publication No. 11-204111 [Patent Document 9] Japanese Patent Application Publication No. 9-007630 [Patent Document 10] USPat.No.6346347 [Patent Document 11] USPat.No.6664002 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0007] Lead-acid batteries are required to have various performance characteristics. Generally, when lignin is added to the negative electrode of a lead-acid battery, the high-rate discharge characteristics are improved and sulfation is suppressed. However, due to its nature, there is a problem that the charge acceptance is reduced.

[0008] An object of the present invention is to provide an organic shrinkage preventer capable of improving the charge acceptance while maintaining the above-mentioned discharge characteristics of the lead-acid battery. [Means for solving the problem]

[0009] As a result of intensive research into the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by subjecting sulfite cooking black liquor to ultrafiltration using an ultrafiltration membrane, thereby reducing the content of substances having a molecular weight of 5,000 or less to 30 mass % of the total, and using this concentrated liquid as an organic shrinkage preventer for lead-acid batteries, thereby completing the present invention.

[0010] That is, the present inventors provide the following [1] and [2]. [1] A method for producing an organic shrinkage preventer for lead-acid batteries containing lignin sulfonic acid, the method comprising the steps of ultrafiltrating sulfite cooking black liquor using an ultrafiltration membrane and recovering a concentrated solution of the sulfite cooking black liquor.

[0011] [2] An organic shrinkage preventer for lead-acid batteries containing lignin sulfonic acid, characterized in that the content of reducing sugars per solid content is 5% by mass or less of the total, and the content of substances having a molecular weight of 5,000 or less per solid content is 30% by mass or less of the total. Effect of the Invention

[0012] According to the present invention, it is possible to improve the charge acceptance of a lead-acid battery while maintaining the discharge characteristics of the lead-acid battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below based on preferred embodiments thereof, but the present invention is not limited to the following embodiments.

[0014] <Organic shrink-proofing agent> The organic shrink-proofing agent of the present invention preferably contains lignin having a methoxyl group content of 3 to 20 mass% based on the solid content. If the methoxyl group content is less than 3%, the amount of lignin contained is so small that the organic shrink-proofing agent is not effective. Generally, lignin contains methoxyl groups bonded to aromatic nuclei, so the methoxyl group content is an index of the lignin content.

[0015] In the present invention, the methoxyl group content is a value measured by the quantitative determination of methoxyl groups by the Viebock and Schwappach method (see "Lignin Chemical Research Methods," pp. 336-340, published by Uni Publishing Co., Ltd. in 1994).

[0016] The lignin used in the organic shrinkage adjuster for lead-acid batteries according to the present invention varies depending on the processing method of woody biomass, and there are several types of lignin.

[0017] The lignin used in the present invention includes the following lignins. For example, lignin sulfonic acid, kraft lignin, soda lignin, soda-anthraquinone lignin, organosolv lignin, explosive lignin, sulfuric acid lignin, etc. are included. Of these, it is preferable to use lignin sulfonic acid. It is particularly preferable to use oxylignin that has been partially desulfonated by reacting lignin sulfonic acid under alkaline conditions at high temperature and high pressure, as described in US Pat. No. 6,346,347.

[0018] The lignin used in the present invention may be in a powder or liquid form, but is preferably in a powder form. For example, the liquid lignin may be prepared by dissolving powdered lignin in a suitable solvent (e.g., water, an aqueous solution of sodium hydroxide, etc.).

[0019] The lignin used in the present invention may be one or a mixture of two or more of the above-mentioned lignins.

[0020] The lignin sulfonic acids used in the present invention will be described in detail below, but are not limited to these lignins.

[0021] (Lignosulfonic acid) Lignosulfonic acid refers to a compound in which at least a portion of lignin or its decomposition products is substituted with a sulfonic acid (salt) group. The lignosulfonic acid of the present invention usually has an S content of the sulfonic acid (salt) group of 1.0 to 10.0 mass%.

[0022] The S content of the sulfonic acid (salt) group of lignosulfonic acid refers to the amount of S contained in the sulfonic acid (salt) group relative to the solid content of lignosulfonic acid. Specifically, it is a value calculated from the following mathematical formula (1).

[0023] Formula (1): S content (mass%) of sulfonic acid (salt) group = total S content (mass%) - inorganic S content (mass%) (In formula (1), the S content indicates the S content relative to the solid content of lignosulfonic acid.)

[0024] In formula (1), the total S content can be quantified by ICP atomic emission spectrometry, and the inorganic S content can be calculated as the sum of the SO3 content and the SO4 content quantified by ion chromatography.

[0025] The organic shrinkage preventer for lead-acid batteries containing lignosulfonic acid of the present invention contains reducing sugars. Reducing sugars generally remain in the process of sulfite digestion of woody biomass. The content of reducing sugars is preferably 5% by mass or less, more preferably 3% by mass or less. By making the content of reducing sugars 5% by mass or less, it is possible to improve the charge acceptance while maintaining the discharge characteristics of the lead-acid battery.

[0026] The reducing sugar refers to a sugar that exhibits reducing properties, and is a sugar that generates an aldehyde group or a ketone group in a basic solution.

[0027] Reducing sugars include, for example, all monosaccharides, disaccharides such as maltose, lactose, arabinose, and invert sugar of sucrose, and polysaccharides. Reducing sugars contained in the alkali treatment effluent usually include cellulose, hemicellulose, and their decomposition products. Decomposition products of cellulose and hemicellulose include, for example, monosaccharides such as rhamnose, galactose, arabinose, xylose, glucose, mannose, and fructose; and oligosaccharides such as xylooligosaccharides and cellooligosaccharides.

[0028] The reducing sugar content can be determined by measuring the reducing sugar content by the Somogyi-Schaffer method and converting the measured value into the amount of glucose.

[0029] The lignosulfonic acid may be in a non-ionized state, or the hydrogen atoms of the sulfonic acid groups may be substituted with counter ions.

[0030] Examples of counter ions include sodium ions, calcium ions, magnesium ions, and ammonium ions.

[0031] The counter ion may be one type of counter ion alone, or two or more types of counter ions may be combined.

[0032] The lignosulfonic acid of the present invention usually contains an inorganic salt. Examples of the inorganic salt include sodium sulfate, sodium sulfite, sodium chloride, magnesium sulfate, magnesium sulfite, magnesium chloride, calcium sulfate, calcium sulfite, calcium chloride, ammonium sulfate, ammonium sulfite, ammonium chloride, and sodium hydroxide. The content of the inorganic salt in the lignosulfonic acid is usually 1 to 25 mass%.

[0033] (Method for preparing lignosulfonic acid) Lignosulfonic acid having a low degree of sulfonation can be prepared, for example, by subjecting lignocellulosic raw materials to a sulfite treatment. Among these, it is preferable to subject lignocellulosic raw materials to a sulfite digestion treatment.

[0034] The lignocellulose raw material is not particularly limited as long as it contains lignocellulose in the structure, and examples thereof include pulp raw materials such as wood and non-wood.

[0035] Examples of wood include coniferous wood such as Yezo spruce, red pine, cedar, and cypress, and broad-leaved wood such as white birch and beech. The age and part of the tree from which the wood is harvested do not matter. Therefore, wood harvested from trees of different ages or from different parts of a tree may be used in combination.

[0036] Examples of non-wood materials include bamboo, kenaf, reed, and rice.

[0037] The lignocellulosic raw material may be one of these materials, or two or more of them may be used in combination.

[0038] The sulfite treatment can be carried out by contacting at least one of sulfurous acid and a sulfite salt with a lignocellulosic raw material to obtain an intermediate product. The conditions for the sulfite treatment are not particularly limited as long as they allow introduction of a sulfonic acid (salt) group to the α-carbon atom of the side chain of lignin contained in the lignocellulosic raw material.

[0039] The sulfite treatment is preferably carried out by sulfite cooking, which allows the lignin in the lignocellulosic raw material to be sulfonated more quantitatively. The sulfite cooking is also called sulfite cooking.

[0040] The sulfite cooking method is a method in which lignocellulosic raw materials are reacted at high temperatures in a solution of at least one of sulfurous acid and a sulfite salt (e.g., an aqueous solution: cooking liquid). This method has been established and is being used industrially as a method for producing sulfite pulp. Therefore, by carrying out the sulfite treatment by the sulfite cooking method, it is possible to improve the economy and ease of implementation.

[0041] When sulfite cooking is carried out, examples of the sulfite salt include magnesium salts, calcium salts, sodium salts and ammonium salts.

[0042] The sulfurous acid (SO2) concentration in at least one of the sulfurous acid and sulfite salt solutions is not particularly limited, but the ratio of mass (g) of SO2 to 100 mL of reaction solution is preferably 1 g / 100 mL or more, and more preferably 2 g / 100 mL or more when sulfite cooking is performed. The upper limit is preferably 20 g / 100 mL or less, and more preferably 15 g / 100 mL or less when sulfite cooking is performed. The SO2 concentration is preferably 1 g / 100 mL to 20 g / 100 mL, and more preferably 2 g / 100 mL to 15 g / 100 mL when sulfite cooking is performed.

[0043] The pH value of the sulfurous acid treatment is not particularly limited, but is preferably 10 or less, and more preferably 5 or less when sulfite cooking is performed. The lower limit of the pH value is preferably 0.1 or more, and more preferably 0.5 or more when sulfite cooking is performed. The pH value during the sulfurous acid treatment is preferably 0.1 to 10, and more preferably 0.5 to 5 when sulfite cooking is performed.

[0044] The temperature of the sulfurous acid treatment is not particularly limited, but is preferably 170° C. or lower, and more preferably 150° C. or lower when sulfite cooking is performed. The lower limit is preferably 70° C. or higher, and more preferably 100° C. or higher when sulfite cooking is performed. The temperature condition of the sulfurous acid treatment is preferably 70 to 170° C., and more preferably 100 to 150° C. when sulfite cooking is performed.

[0045] The treatment time for the sulfurizing treatment is not particularly limited, and although it depends on the conditions of the sulfurizing treatment, it is preferably 0.5 to 24 hours, more preferably 1.0 to 12 hours.

[0046] In the sulfite treatment, it is preferable to add a compound that supplies a counter cation (salt). By adding a compound that supplies a counter cation, the pH value in the sulfite treatment can be kept constant. Examples of compounds that supply counter cations include MgO, Mg(OH)2, CaO, Ca(OH)2, CaCO3, NH3, NH4OH, NaOH, NaHCO3, and Na2CO3. The counter cation is preferably a magnesium ion.

[0047] In the sulfurous acid treatment, when a solution of at least one of sulfurous acid and sulfite is used, the solution may contain, in addition to SO2 and a counter cation (salt), a digestion and penetration agent (e.g., a cyclic ketone compound such as anthraquinone sulfonate, anthraquinone, or tetrahydroanthraquinone) as necessary.

[0048] There is no limitation on the equipment used in the sulfite treatment, and for example, generally known dissolving pulp manufacturing equipment can be used.

[0049] The intermediate product may be separated from the solution of at least one of sulfurous acid and sulfite salts by a conventional method, for example, a method for separating sulfite digestion wastewater after sulfite digestion.

[0050] The sulfite digestion process may produce lignosulfonic acid with a high degree of sulfonation, in which case a partial desulfonation process can produce lignosulfonic acid with a low degree of sulfonation. Examples of partial desulfonation methods include, but are not limited to, those described in US Pat. No. 2,371,136 and JP-A-58-45287.

[0051] Also, lignosulfonic acid with a low degree of sulfonation can be obtained by the method described in JP 2016-135834 A.

[0052] The method for producing an organic shrink-proofing agent containing lignin sulfonic acid of the present invention includes a step of ultrafiltrating sulfite cooking black liquor using an ultrafiltration membrane (UF membrane) to recover a concentrated liquid.

[0053] By ultrafiltrating black liquor using a UF membrane, liquid lignin can be recovered as a component of the concentrated liquid. Furthermore, the ultrafiltration process can separate high molecular weight lignin from other components. In other words, liquid lignin can be produced from black liquor using a UF membrane.

[0054] (UF membrane) As the UF membrane, any known UF membrane can be used, including, for example, a hollow fiber membrane, a spiral membrane, a tubular membrane, and a flat membrane.

[0055] The material of the UF membrane may be any known material. For example, cellulose acetate, aromatic polyamide, polyvinyl alcohol, polysulfone, polyvinylidene fluoride, polyethylene, polyacrylonitrile, and ceramic may be used. The UF membrane may be a commercially available product.

[0056] The molecular weight cutoff of the UF membrane is preferably 5,000 to 30,000, more preferably 10,000 to 25,000, and even more preferably 15,000 to 23,000. When a UF membrane with a molecular weight cutoff of 5,000 or more is used, it is possible to prevent the separation speed of the black liquor from being excessively slowed. In addition, when a UF membrane with a molecular weight cutoff of 30,000 or less is used, it is possible to prevent lignin from being unable to be separated from the black liquor.

[0057] Ultrafiltration using a UF membrane is divided into two steps: concentration and volumetric adjustment. Either one of the two steps may be performed, or both may be performed. When both steps are performed, volumetric adjustment is preferably performed after concentration.

[0058] The concentration ratio by ultrafiltration using a UF membrane can be set as desired. In other words, the ultrafiltration can be stopped when the amount of permeate flowing out reaches a desired amount. It is preferable to concentrate the solution 2 to 6 times. For example, a 4-fold concentration means that the amount of permeate that has permeated the UF membrane becomes 3 / 4 of the amount of the solution before treatment.

[0059] The constant volume ratio by ultrafiltration using a UF membrane can be set arbitrarily. That is, water is added while keeping the volume of the concentrated liquid constant, and the ultrafiltration process can be stopped when the permeate reaches a desired volume. It is preferable to add 0.5 to 3 times the amount of water to the concentrated liquid to make the volume constant. For example, a constant volume of 2 times means that the amount of the permeate is doubled from the amount of the raw liquid before treatment by adding water to the raw liquid while keeping the amount of the raw liquid (black liquor) constant and performing ultrafiltration.

[0060] (Ultrafiltration process) The temperature of the black liquor during ultrafiltration is not particularly limited, and is preferably 20 to 80°C, and more preferably 20 to 70°C in consideration of the heat resistance of the UF membrane material.

[0061] The pH value of the black liquor during the ultrafiltration treatment is preferably 2 to 11.

[0062] The solids concentration (w / w) of the black liquor during ultrafiltration is preferably from 2 to 30%, more preferably from 5 to 15%.

[0063] (Concentrate) In the concentrated solution, the content of substances having a molecular weight of 5,000 or less is preferably 30 mass% or less, and more preferably 20 mass% or less. If the content of substances having a molecular weight of 5,000 or less exceeds 30 mass%, the concentrated solution contains a large amount of low molecular weight impurities, and the charge acceptance of the lead-acid battery does not improve.

[0064] The molecular weight of the lignin in the concentrate after ultrafiltration can be measured by gel permeation chromatography (GPC). The GPC measurement may be performed under the following conditions using a known method in which the molecular weight is converted into pullulan.

[0065] Measuring device: Tosoh Columns used: Shodex Column OH-pak SB-806HQ, SB-804HQ, SB-802.5HQ Eluent: 1.0% sodium tetraborate, 0.3% isopropyl alcohol in water Eluent flow rate; 1.00ml / min Column temperature: 50°C Measurement sample concentration: 0.2% by mass Standard substance: Pullulan (Showa Denko) Detector: RI detector (manufactured by Tosoh) Calibration curve; Pullulan standard

[0066] The weight average molecular weight of the lignin in the concentrated liquid after ultrafiltration is preferably 10,000 to 40,000, and more preferably 20,000 to 35,000.

[0067] The content of lignin having a molecular weight of 5,000 or less in the concentrate can be calculated as follows. First, the concentrate is measured by GPC under the above-mentioned conditions to obtain a GPC chromatogram with peak intensity (mV) on the vertical axis and retention time on the horizontal axis. The baseline is usually taken to be from the start of elution of the polymer peak to the end of elution. If the end of elution time is not clearly observed, the baseline is created and then divided at the midpoint between the peak and the valley of the peak, and this point is taken as the end of elution of the polymer peak. Since the GPC chromatogram of lignin does not usually give a clear peak, the polymer elution curve including multiple peaks is taken as one peak from the start of elution of the polymer peak, and the peak is divided vertically at the position of the molecular weight of 5,000, and the area ratio is calculated.

[0068] The organic shrinkage inhibitor of the present invention is mainly added to the negative electrode plate of a lead-acid battery, and the addition rate is usually 0.02 to 1.0 mass % based on the lead powder.

[0069] The lead-acid batteries using the organic shrinkage inhibitor for lead-acid batteries of the present invention can be used as automobile batteries, batteries for portable devices, backup batteries for computers, batteries for communications, and the like. EXAMPLES

[0070] The present invention will now be described in more detail with reference to examples. The following examples are provided to suitably explain the present invention and are not intended to limit the present invention.

[0071] <Ultrafiltration of black liquor> Sanex M100 (manufactured by Nippon Paper Industries Co., Ltd., concentration 12%, main component: lignin sulfonic acid) was concentrated 4 times by ultrafiltration (molecular weight cutoff 20,000), and the volume was adjusted to 1.0 times, and the resulting concentrated liquid was powdered in a vacuum dryer (105°C, 24 hours) to obtain lignin sulfonic acid powder (Lignin 1). Sanex M100 was also concentrated 4 times by ultrafiltration (molecular weight cutoff 12,000), and the volume was adjusted to 1.0 times, and the resulting concentrated liquid was powdered in a vacuum dryer (105°C, 24 hours) to obtain lignin sulfonic acid powder (Lignin 2). Sanex M100 was also powdered without ultrafiltration to obtain lignin sulfonic acid powder (Lignin 3).

[0072] The physical properties of Lignins 1 to 3 are shown in the following Table 1. In addition, % in Table 1 indicates % relative to the solid content.

[0073] [Table 1]

[0074] <Creating a lead-acid battery> The lead acid battery positive electrode active material paste of this embodiment and the comparative example was manufactured as follows according to JP-A-9-237632. First, lead powder containing 70-80% by weight of lead monoxide, 13% by weight of dilute sulfuric acid (specific gravity 1.26: 20°C) relative to the lead powder, and 12% by weight of water relative to the lead powder were kneaded to prepare a positive electrode active material paste. About 25 g of the above paste-like positive electrode active material was filled into a current collector made of a lead alloy grid, and then left (aged) at 80°C for 24 hours in a nitrogen atmosphere without being dried to obtain an unformed positive electrode plate.

[0075] Next, lead powder containing 70-80% by weight of lead monoxide, 13% by weight of dilute sulfuric acid (specific gravity 1.26 at 20°C) based on the lead powder, 12% by weight of water based on the lead powder, 1.2% by weight of barium sulfate, and 0.3% by weight of an organic shrinkage inhibitor were added and kneaded to prepare a negative electrode active material paste. Approximately 25 g of this negative electrode active material paste was filled into a current collector made of a lead alloy grid, and then left (aged) at 80°C for 24 hours in a nitrogen atmosphere without being dried to obtain an unformed negative electrode plate.

[0076] The negative and positive electrodes obtained by the above-mentioned manufacturing method were combined to prepare a lead-acid battery with a rated capacity of 28 Ah-2 V.

[0077] (High rate discharge characteristic test) A 150A high rate discharge characteristic test was carried out in accordance with JIS D5301. The discharge duration was evaluated. The longer the discharge duration, the better the evaluation.

[0078] (Charging acceptance test) A charge acceptance test was conducted in accordance with JIS D5301. The charge current was evaluated 10 minutes after the start of charging. The higher the current value, the better the evaluation.

[0079] (5-hour rate capacity test) A 5-hour capacity test was conducted in accordance with JIS D5301. The discharge duration was evaluated. The longer the discharge duration, the better the evaluation.

[0080] The test results are shown in Table 2.

[0081] [Table 2]

[0082] As shown in Table 2, the organic shrinkage preventers for lead-acid batteries of the present invention in Examples 1 and 2 had almost the same high-rate discharge characteristics and excellent charge acceptance as the organic shrinkage preventers for lead-acid batteries of the comparative example. In addition, the organic shrinkage preventers for lead-acid batteries of the present invention in Examples 1 and 2 also had a superior 5-hour rate capacity as compared to the organic shrinkage preventers for lead-acid batteries of the comparative example.

Claims

1. An organic shrinkage preventer for lead-acid batteries, comprising lignin sulfonic acid, characterized in that the content of reducing sugars per solid content is 5% by mass or less of the total, and the content of substances having a molecular weight of 5,000 or less per solid content is 30% by mass or less of the total.

2. A method for producing an organic shrinkage inhibitor for lead-acid batteries for producing the organic shrinkage inhibitor for lead-acid batteries of claim 1, comprising the steps of ultrafiltrating sulfite digestion black liquor using an ultrafiltration membrane having a molecular weight cutoff of 5,000 to 30,000, and recovering the resulting concentrated solution of the sulfite digestion black liquor.

Citation Information

Patent Citations

  • Organic expanding agent sulfonated lignin preparation method and uses

    CN105131306A

  • Sealed lead storage battery

    JP1987145655A

  • Production of waste liquor of sodium sulfite pulp having low glauber'S salt content

    JP1995018595A

  • Lignin compound to be added to lead-acid battery, its manufacture, and lead-acid battery

    JP1997007630A

  • Negative electrode plate for lead-acid battery

    JP1997147872A